Traditional practice, bioactivities and commercialization potential of Elephantopus scaber Linn - Wan, Yong Ho; Huynh, Ky; Swee, Keong Yeap; Abdul Rahim, Raha; Omar, Abdul Rahman; Chai, Ling Ho; Mohamed Alitheen, Noorjahan Banu (Academic Journals, 2009)
Elephantopus scaber Linn. is known as Prickly-leaves elephant’s foot or di dan tou in Chinese. It has been used in traditional medicine to stimulate diuresis, reduce fever and eliminate bladder stones, as well as to treat nephritis, edema, dampness, chest pain, pneumonia, scabies, arthralgia and leukemia. A number of phytochemicals have also been isolated from this plant, such as deoxyelephantopin, 11,13, dihydrodeoxyelephantopin, lupeol, epifriedelinol and stigmasterol. Most of the major studies only involved the bioactivities of the compounds especially deoxyelephantopin. The effects of the plant extract which can benefit a broad mass of people are still lacking. This paper briefly reviews the traditional usage and scientifically proven bioactivities of E. scaber which contributed its commercialization potential.